Strategic Solutions for Strengthening Mustahik Family Resilience Through Zakat Management Based on Maqashid Al-Shari’ah - Syarto Syarif; Mustafa KamÃ l Rokan; Muhammad Yafiz (FASYA Press, 2025)
This study analyzes the role of zakat in strengthening the economic resilience of mustahik families in Medan City through the framework of maqashid al-shariah. The research employs the Analytic Network Process (ANP) to identify and prioritize key problems, solutions, and strategies in zakat management. Data were collected through a literature review, in-depth interviews with zakat practitioners, religious leaders, academics, and mustahik, and pairwise comparison questionnaires to capture the interdependencies among issues. Unlike conventional prioritization methods, ANP allows the analysis of both inner and outer dependencies, enabling a more comprehensive assessment of the relative importance of each factor. The findings show that the most critical problem is the dominance of consumptive zakat distribution (weight = 0.298), followed by limited assistance and mentoring for mustahik (weight = 0.255), low quality of amil human resources (weight = 0.170), weak mustahik data management (weight = 0.155), and low muzakki trust (weight = 0.122). These results indicate that zakat management still tends to focus on short-term relief rather than sustainable economic empowerment. Strategic solutions include increasing the allocation of productive zakat, strengthening amil human resource capacity, improving mustahik mentoring, digitalizing data and monitoring systems, and promoting zakat programs based on maqashid al-shariah. Implementation strategies emphasize regulatory frameworks requiring at least 50% productive zakat allocation, collaborative governance with religious leaders and local government, the development of a maqashid-based evaluation index, and partnerships with universities and mosques. The study contributes theoretically by positioning maqashid al-shariah as an evaluative framework in zakat governance and methodologically by demonstrating the usefulness of ANP in analyzing complex social finance systems, while providing practical policy insights for sustainable empowerment and increased public trust.